Surgical Management of Large (≥3 cm) Trigeminal Schwannomas: Functional Outcomes and Approach Selection in Multicompartmental Schwannomas - Dwarakanath, Srinivas; Deora, Harsh; Mehta, Sarthak; Shukla, Dhaval; A., Arivazhagan; Rao, KVLN; Somanna, Sampath (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction Trigeminal schwannoma surgery has shown a remarkable improvement in functional recovery and tumor resection. In the era of radiosurgery, these outcomes need to be characterized for tumors which are outside the realm of being treated with radiosurgery. We present a series of trigeminal schwannomas larger than 3 cm, surgical approaches used, and outcomes with an emphasis on functional recovery in a high-volume center with radiosurgery facilities.Method All consecutive cases of trigeminal schwannoma from January 2012 to May 2021 which were more than 3 cm in size and underwent microsurgery were included in this series. The surgical approach, neurological outcomes, and extent of resection were defined objectively with pre/postoperative magnetic resonance imaging.Results A total of 83 such cases (>3 cm) were found, with cranial nerve symptoms (5th most common) being the commonest. Twenty three percent cases had blindness due to secondary optic atrophy and eighteen percent had long tract motor symptoms signifying the tumor burden in our series. Radiological gross total excision was achieved in 75.9% cases.Conclusion Large-volume schwannomas present with cranial nerve involvement and may need extensive skull base approaches. Functional outcomes need to be prioritized and can be achieved albeit with lesser gross resection rates. Hearing and facial preservation in addition to relief of trigeminal symptoms should be the goal of resection with minimal additional morbidity.
Keywords: trigeminal; schwanomma; microsurgery; radiosurgery